2016
DOI: 10.1128/mbio.01425-16
|View full text |Cite
|
Sign up to set email alerts
|

Bats, Primates, and the Evolutionary Origins and Diversification of Mammalian Gammaherpesviruses

Abstract: Gammaherpesviruses (γHVs) are generally considered host specific and to have codiverged with their hosts over millions of years. This tenet is challenged here by broad-scale phylogenetic analysis of two viral genes using the largest sample of mammalian γHVs to date, integrating for the first time bat γHV sequences available from public repositories and newly generated viral sequences from two vampire bat species (Desmodus rotundus and Diphylla ecaudata). Bat and primate viruses frequently represented deep bran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 41 publications
1
42
0
5
Order By: Relevance
“…While some viruses have been detected in bats of phylogenetically distinct clades [63], others groups of viruses are thought to have closely evolved with a single species. New evolutionary analyses of herpesviruses, however, have recently demonstrated that these historic lineages may be comprised of more frequent host-switching events than previously thought [64]. Also, while some viruses are hosted by multiple species, specific strains of a viral species may be constrained to bats of a single species or phylogenetically related hosts [28].…”
Section: Viral Sharing Among Bat Speciesmentioning
confidence: 99%
“…While some viruses have been detected in bats of phylogenetically distinct clades [63], others groups of viruses are thought to have closely evolved with a single species. New evolutionary analyses of herpesviruses, however, have recently demonstrated that these historic lineages may be comprised of more frequent host-switching events than previously thought [64]. Also, while some viruses are hosted by multiple species, specific strains of a viral species may be constrained to bats of a single species or phylogenetically related hosts [28].…”
Section: Viral Sharing Among Bat Speciesmentioning
confidence: 99%
“…Herpesviruses were first detected in bats in 1996 (Tandler 1996). Subsequent work shows that bats likely played a critical role in the evolution and diversification of herpesviruses (Escalera-Zamudio et al 2016). Bats generally have a negative reputation as carriers of deadly viruses that cause human diseases such as rabies, Nipah, and SARS (Wibbelt et al 2010), and consequently, most research on bat viruses has focused on these pathogens of concern for public health.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple bat species come into close proximity within caves where they roost, presenting an opportunity for cross-species viral dispersal. Indeed, cross-species transmission and host switching are common, and have likely been the norm throughout the evolutionary history of the herpesvirus lineage, especially in bat hosts (Escalera-Zamudio et al 2016, Zheng et al 2016, Azab et al 2018, Wada et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…While an increasing number of studies suggest that most animal species harbour their own set of herpesviruses, those of rodents in particular have become a focus in recent years [1, 4, 5]. This is less out of concerns about zoonotic potential but more so because they might provide a practical model for the herpesvirus biology and pathology of human herpesviruses [8-10].…”
Section: Introductionmentioning
confidence: 99%
“…Herpesviruses are largely host specific and have to a large part co-evolved with their host species. However, cross-species transmission has probably occurred in the past and contributed to the herpesvirus evolution [5]. Several examples of presently circulating herpesvirus species underline this capacity to crossover into related host species, such as Ovine herpesvirus 2 (OvHV-2) and the Alcelaphine herpesvirus 1 (AlHV-1), which both do not induce clinical symptoms in their reservoir hosts, but cause malignant catarrhal fever in cattle and other ungulates [6].…”
Section: Introductionmentioning
confidence: 99%